Perancangan Fasilitas Produksi dengan menggunakan Metode Computerized Relative Allocation of Facilities Technique (CRAFT) pada UMKM Gethuk Lindri Niki Eco - Sasongko Fiqri Wahyu Illahi; Bekti Nugrahadi; Anita Oktaviana Trisna Devi (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The development of MSMEs in the traditional food sector requires business actors to increase production capacity. MSME Gethuk Lindri Niki Eco plans to build a larger facility to meet increasing demand. However, the layout planning is still based on rough drawings and experience, which can lead to inefficient material movement. This study aims to provide an overview of recommendations for a more efficient production facility layout using the CRAFT method. The research method involves collecting data on production processes, departmental areas, and material movement frequency. Moreover, an Activity Relationship Chart (ARC) is compiled to identify the close relationships among departments. The results of the analysis are visualized with a Block Plan. Furthermore, the layout is optimized using the CRAFT method. The results show that the recommended layout reduces the total material movement distance from 60.96 meters to 58.19 meters or a reduction of 4.53%. In addition, material handling costs also decreased from Rp. 780.64 to Rp. 766.19 or a savings of 1.85%. Thus, the application of the CRAFT method resulted in a more efficient production layout at the Gethuk Lindri Niki Eco MSME.